Kode Etik Auditor: Telaah Model Auditing Rasulullah SAW, Sebagai Role Model Auditor - Sari, Fika Hartina; Jumliana, Melsa; Kamal, Nur Asmi Ainun (JCA (Jurnal Cendekia Akuntansi), 2024)
Auditor ethics play a crucial role in maintaining integrity, transparency, and accountability in the audit process. This study aims to examine the auditing model taught by the Prophet Muhammad SAW and explore the relevance of his ethical principles as a role model for auditors in the context of professionalism, independence, objectivity, communication, confidentiality, and accountability. In this study, it was identified that the Prophet Muhammad SAW, as a leader and individual who has great responsibility in leading the people, practiced ethical values ​​that are very relevant to the modern audit world. Through his example in carrying out his duties fairly, maintaining trust, effective communication, and steadfastness in being accountable for every decision, the Prophet Muhammad SAW provided strong guidance for auditors in carrying out their profession. The honesty, transparency, and justice applied by the Prophet Muhammad SAW in all aspects of his life are important foundations in building trust and professionalism in auditing. Therefore, the auditing model taught by the Prophet Muhammad SAW is not only relevant to Muslims, but also makes a significant contribution to the development of ethical audit practices in the modern era.